Relative transfer function (RTF) estimation utilising peaks in time‐domain RTF. Issue 14 (1st July 2016) - Shin, M.; Kim, W.; Han, D.K.; Ko, H.
Abstract : An effective algorithm for a more accurate estimation of relative transfer function (RTF) to improve the directional‐blind source separation‐based RTF estimation is presented. The peaks in time‐domain RTF (PTDR) as a feature of time‐domain RTF to improve the conventional algorithm are utilised. The PTDRs contain important characteristics of RTF; however, they are smoothed due to the geometric constraint in the conventional algorithm. In the proposed algorithm, the PTDRs are recovered by employing the semi‐non‐negative matrix factorisation algorithm to effectively find the PTDRs from other peaks. A series of experiments using interfere and various noises demonstrates effectiveness of the proposed RTF estimation algorithm utilising the PTDR.